A new forum for research on research integrity and peer review - Harriman, S; Kowalczuk, M; Simera, I; Wager, E (BioMed Central, 2016)
This editorial explains why we are launching Research Integrity and Peer Review, a new open-access journal that will provide a home to research on ethics, reporting, and evaluation of research. We discuss how the idea to launch this journal came about and identify the gaps in knowledge where we would like to encourage more research and interdisciplinary discussion. We are particularly keen to receive submissions presenting actual research that will increase our understanding and suggest potential solutions to issues related to peer review, study reporting, and research and publication ethics.